Implikasi Standar dan Jenis Penilaian dalam Pembelajaran Pendidikan Agama Kristen di Gereja - Lusia Rahajeng (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Christian religious education is a vital aspect of church teachings, as it shapes an individual's character and spiritual attitude. However, ensuring the quality and effectiveness of religious education requires appropriate standards and types of assessments in the learning process. This study aimed to analyze the implications of standards and types of assessments in Christian religious education in churches. The research employed a document analysis approach, collecting data from various sources such as textbooks, journal articles, and official documents from churches. The analysis identified the standards that should be met in Christian religious education, including theological understanding, prayer practice, participation in worship, moral and ethical understanding, and personal development activities. The research also evaluated appropriate types of assessments to evaluate students' achievements in meeting these standards, such as formative and summative assessments, project assessments, portfolio assessments, and direct observation. Educators should understand the standards that must be met in religious education and choose the appropriate types of assessments to evaluate students' achievements. The study's findings can serve as a reference for churches in developing quality learning programs and ensuring effective implementation of religious education. In conclusion, Christian religious education in churches plays a crucial role in shaping an individual's character and spiritual attitude. The study highlights the importance of using appropriate standards and types of assessments to ensure the quality and effectiveness of learning. Educators and churches should work together to provide adequate support and resources to facilitate effective learning implementation.